2008
DOI: 10.1111/j.1551-2916.2008.02442.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Property Phase Diagram of BaZrxTi1−xO3 System

Abstract: In the course of searching environmental friendly lead‐free relaxor ferroelectrics a complete phase diagram of barium zirconate titanate, Ba(ZrxTi1−x)O3 system with compositions 0.00≤x≤1.00 has been developed based on their dielectric behavior. It has been shown that BaZrxTi1−xO3 system depending on the composition, successively depicts the properties extending from simple dielectric (pure BaZrO3) to polar cluster dielectric, relaxor ferroelectric, second order like diffuse phase transition, ferroelectric with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
197
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(228 citation statements)
references
References 55 publications
30
197
1
Order By: Relevance
“…[35]: for T > T b we have a(T ) ∝ (T − T 0 ), while for T < T m we have da(T )/dT ∼ 0, and for T m < T < T b we have a smooth interpolation between these two regimes (note that (i) T 0 is extracted from the Curie-Weiss behavior of the dielectric response above T b and can be negative in relaxor ferroelectrics, as predicted and experimentally found in Refs. [35,37] ; and (ii) that the aforementioned behaviors of a(T ) implies that it is increasing with temperature above T m ). In the following equations we will work with a generic a(T ) > 0, noting that the final results have to be interpreted depending on the T region we are in.…”
Section: B Analysis Of the Results Via A Landau-like Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[35]: for T > T b we have a(T ) ∝ (T − T 0 ), while for T < T m we have da(T )/dT ∼ 0, and for T m < T < T b we have a smooth interpolation between these two regimes (note that (i) T 0 is extracted from the Curie-Weiss behavior of the dielectric response above T b and can be negative in relaxor ferroelectrics, as predicted and experimentally found in Refs. [35,37] ; and (ii) that the aforementioned behaviors of a(T ) implies that it is increasing with temperature above T m ). In the following equations we will work with a generic a(T ) > 0, noting that the final results have to be interpreted depending on the T region we are in.…”
Section: B Analysis Of the Results Via A Landau-like Modelmentioning
confidence: 99%
“…Since we are also interested in checking if and how this difference (if any) depends on the investigated temperature region, we decided to focus on four particular representative temperatures. They are: (1) 500 K, which is above the predicted Burns temperature (T b ≃ 450 K) of BZT [35,37]; (2) 300 K, which is located in-between our critical T * ≃ 240 K [33][34][35] and T b ; (3) 200 K, that is now between the computed T m temperature of BZT (T m ≃ 130 K) [35,38] and T * ; and (4) 100 K, which is thus below T m (note that the Supplemental Material [54] also shows our results for the EC coefficient in BZT at 600 K). Figure 2 shows the electrocaloric coefficient as a function of electric field, E, for these four different selected temperatures, and as computed from the aforementioned MC-1, MC-2 and MD methods.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, all the aforementioned questions are addressed by investigating, analysing and comparing with experiments the complex dielectric response of disordered BZT crystal numerically obtained in the THz regime, via a combination of a first-principles-based effective Hamiltonian and a molecular dynamics (MD) technique. BZT is chosen because it is a lead-free relaxor that has already attracted a lot of attention 19,27,38,[44][45][46][47][48] . In relaxors, most experimental works were performed in the kilohertz regime, which is (unfortunately) not accessible by our MD techniques.…”
mentioning
confidence: 99%
“…Furthermore, the phase transition of this system changes from a "normal" ferroelectric to a typical relaxor behavior by increasing zirconium concentration (until x = 0.75) [16][17][18][19][20][21] which is caused by the inhomogeneous distribution of [ZrO 6 ] clusters into the titanium (Ti) sites and/or by the mechanical stresses on the grains [19]. A polar cluster like behavior is obtained for Zr-rich BZT compositions (x > 0.75) [17]. Present composition BaZr 0.25 Ti 0.75 O 3 is chosen as the host material because it shows relaxor behavior and detailed optical, structural and dielectric studies have been reported by Ref.…”
Section: Introductionmentioning
confidence: 99%